Collaborative Governance in Handling Cases of Violence Against Women and Children in Kupang City - Piter Anderias LENAMAH; William DJANI; Laurensius Petrus SAYRANI (PT Keberlanjutan Strategis Indonesia, 2025)
Violence against women and children in Kupang City is a serious problem that requires an integrated approach. Collaborative governance is a crucial strategy for strengthening cross-actor coordination in addressing this issue. This study aims to analyze collaborative practices in handling cases of violence against women and children in Kupang City. The method employed is a qualitative case study, utilizing data collection techniques that include interviews with 17 informants, observation, and document analysis. The results of the study indicate that the Kupang City Women's Empowerment and Child Protection Service (DP3A) plays a central role in building partnerships with various actors, including the police, legal aid institutions, civil society organizations, and international partners. This study demonstrates that the capacity for joint action is built upon a track record of collaboration, alignment of procedures, and public trust despite being limited by budget, expertise, and supporting facilities. Collaboration is facilitated by formal regulations and informal agreements and supported by transparency through coordination forums and the publication of information on digital media. Responsive, initiative and proactive leadership strengthen decision-making. The collaborative process involves regular meetings, participation from target groups, communication within networks, and shared commitments, resulting in community empowerment, child involvement in advocacy, and enhanced victim assistance. Recommendations include establishing regional regulations, recognizing the contributions of community volunteers, providing ongoing training, and enhancing inclusive public communication strategies to promote a more cohesive community.